THE ROLE OF RESEARCH WORK IN PERSONNEL TRAINING - Ismatullaeva Kholida Zakrullaevna; Daminova Rano Basitovna (Journals Park Publishing, 2025)
The main goal of organizing and developing students' research work is to increase the level of scientific training of specialists with higher professional education. Students' research work is a continuation and deepening of the educational process. Research work develops their creativity, skills and abilities, and increases their motivation to study the taught sciences.
Keywords: Research work, educational process, specialists, professional education, ability, skills, motivation, professionalism.